Angiogenesis in nasopharyngeal carcinoma: insights, imaging, and therapeutic strategies - Xia, Chenxi; Zhao, Jia; Huang, Yu; Miao, Hongbin; Zhao, Feipeng (Frontiers in Oncology, 2024)
Nasopharyngeal carcinoma (NPC) is a highly prevalent head and neck malignancy in southern China frequently diagnosed at advanced stages owing to subtle early symptoms and associated metastasis. Angiogenesis emerges as a pivotal factor in NPC progression, with numerous angiogenesis-related factors showing aberrant expression and contributing to increased neovascularization within NPC tumors. These abnormal vessels not only nourish tumor growth but also facilitate metastasis, culminating in unfavorable patient outcomes. Multiple studies have demonstrated the applicability of various imaging techniques for assessing angiogenesis in NPC tumors, thus serving as a foundation for personalized treatment strategies and prognostic assessments. Anti-angiogenic therapies have exhibited significant potential for inhibiting NPC angiogenesis and exerting anti-tumor effects. To enhance efficacy, anti-angiogenic drugs are frequently combined with other treatment modalities to synergistically enhance anti-tumor effects while mitigating the side effects associated with single-agent therapies, consequently improving patient prognosis. Identifying the potential mechanisms and key targets underlying NPC angiogenesis and exploring more effective detection and treatment approaches holds promise for shaping the future of NPC diagnosis, treatment, and prognosis, thereby offering new avenues and perspectives for research and clinical practice.